Correction: Desterke et al. Single-Cell RNA-Seq Analysis Links DNMT3B and PFKFB4 Transcriptional Profiles with Metastatic Traits in Hepatoblastoma. Biomolecules 2024, 14, 1394 - Christophe Desterke; Raquel Francés; Claudia Monge; Agnès Marchio; Pascal Pineau; Jorge Mata-Garrido (Biomolecules)
In the published publication [...]